Quantifying mechanical properties of material extrusion fabricated lattice structures based on semi-rigid joint frame formulation - Park, Sang-In (2016)
This paper presents a new numerical modeling scheme based on the semi-rigid joint frame element formulation for lattice structures fabricated using material extrusion. The proposed scheme has two main elements. First, a modified semi-rigid joint frame element is formulated in order to model struts in lattice structures. Second, a voxel model is developed by simulating the material deposition process; the resulting model geometry is similar to that of the fabricated part. Using this model, effective structural parameters, such as effective strut and joint size and effective joint stiffness, can be computed. Parametric studies were conducted to examine manufacturing effects on the structural parameters. Estimated mechanical properties utilizing the proposed modeling approach are compared with tensile test results for three types of lattice structures. Results demonstrate good predictive capability of the proposed modeling approach.